Insights into the defensive roles of lncRNAs during Mycoplasma pneumoniae infection - Yang, Zhujun; Zhou, Junjun; Su, Nana; Zhang, Zifan; Chen, Jiaxin; Liu, Peng; Ling, Peng (Frontiers in Microbiology, 2024)
Mycoplasma pneumoniae (M. pneumoniae) causes respiratory tract infections, affecting both children and adults, with varying degrees of severity ranging from mild to life-threatening. In recent years, a new class of regulatory RNAs called long non-coding RNAs (lncRNAs), haves been certificated found to play a crucial roles in regulating gene expression in the host. The analysis ofResearch on lncRNAs hasve greatly expanded our understanding of cellular functions involving RNAs molecules, and haveit has significantly increased the range of functions of lncRNAsthat were previously thought to be exclusive to coding RNAs. In the case of lung canceradenocarcinoma, transcripts associated with lncRNAs have been identified as regulators of airway and lung inflammation caused by M. pneumoniaein a process involving. These transcripts functions through the involvement of a protein complexes.TheAn excessive immune response and antibacterial immunity are closely linked to the pathogenesis of M. pneumoniae. The relationship between lncRNAs and M. pneumoniae infection is largely attributed to the role of involves lncRNAs inthat participate in 带格式的: 居中